The Concept of Development in Ibnu Khaldun's Thought - Rasyid Thaha; Aiman Sabar Rezeky (Borong Newinera Publisher, 2023)
Development is a complex and multidimensional process involving social, economic, political and environmental aspects in a society or country. Initially, development was interpreted as a process that only involved economic aspects. However, along with the development of empirical thinking and experience, the concept of development is developing and involving other aspects such as social, political and environmental aspects. Ibnu Khaldun as a philosopher also had special thoughts regarding the concept of development by using Islamic religious values as the basis of his thinking. This article was written using a qualitative method with descriptive presentation and using secondary data in the form of literature study. The results of writing this article illustrate that the concept of development in Ibn Khaldun's thinking is a social process related to the progress of society from one level of civilization to a higher level. This process occurs through three phases: formation, growth, and decline. Ibnu Khaldun also offered solutions for building the nation and state with three approaches, namely: First, starting development with a focus on the quality of human resources, Second, strengthening government solidly and Third, prioritizing human development over physical development. Ibnu Khaldun also offered the concept of development, especially in the economic sector, which consists of four important roles, namely: First, the role of humans or Ar-Rijal, Second, the link between development or Al-Imarah and justice or Al-Adl, Third, the role of institutions and government, and Fourth, the role of wealth or Al-Mal. Ibn Khaldun's views are still relevant today and can provide inspiration for sustainable development in the future.